Peru in the Trans-Pacific Partnership (TPP): Benefits and Myths - Castillo Mezarina, José Luis (2016)
The Trans-Pacific Partnership Agreement (TPP) is the first mega-regional trade agreement of the XXI century. It is composed of twelve economies of three continents, all members of the Asia-Pacific Economic Cooperation (APEC).Peru’s participation in this exceptional agreement means winning five new markets in a single trade agreement: Australia, Brunei Darussalam, New Zealand, Malaysia and Vietnam. The potential increase in non-traditional Peruvian exports to those markets by the entry into force of the TPP Agreement is estimated in US$ 2,250 million. The country also gains by improving in TPP the conditions of access and trade rules of previous bilateral agreements.One of the biggest gains from TPP for developing economies like Peru is the access to global value chains, as a result of the application of a mechanism known as «origin accumulation». This mechanism will particularly benefit SMEs, as inputs they export can be introduced in a value chain of the TPP trading bloc.Regarding myths about negative impacts of the TPP, specifically about a supposed rise in prices of medicines, alleged millionaire losses in Investor-State Dispute Settlement arbitrations, and alleged restrictions on freedoms in the Internet, it is not true that the TPP Agreement generates adverse effects in these areas The same myths were spread during of the US-Peru Trade Promotion Agreement negotiations, and none of it happened in reality.